1997
DOI: 10.1002/bjs.1800840324
|View full text |Cite
|
Sign up to set email alerts
|

Indications and results of local treatment of rectal cancer

Abstract: Patients with pT1 rectal tumours represent a suitable group for local treatment because of the acceptability of the procedure and the low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 28 publications
2
37
0
5
Order By: Relevance
“…If it is unclear that the TEM resection was radical, it is essential (and recommended) that an anterior resection be subsequently performed. This was the decision made in 12% of cases in our present series and in 21.4% of cases in the largest series reported by Buess's group [2]. In a series of 113 patients, Buess et at.…”
Section: Limitations Of Tem For Treatment Of Cancermentioning
confidence: 66%
See 1 more Smart Citation
“…If it is unclear that the TEM resection was radical, it is essential (and recommended) that an anterior resection be subsequently performed. This was the decision made in 12% of cases in our present series and in 21.4% of cases in the largest series reported by Buess's group [2]. In a series of 113 patients, Buess et at.…”
Section: Limitations Of Tem For Treatment Of Cancermentioning
confidence: 66%
“…Moreover, the duration of hospitalization (5.7 days for TEM versus 14.5 days, p < 0.0001) [11] and the complication rate (21% versus 35%) [ll] ar e significantly lower than those reported for low anterior resection. Overall, the localized complication rate associated with transanal resection lies between 4.0% and 8.3% of cases [2,12] and that for systemic complications between 14% and 21% ( Table Table 3 (Table 3), only one German study reported a fatality: a unique, lethal complication of retroperitoneal phlegmon after TEM resection of an adenoma located 7 cm from the anal verge in a 55-year-old patient who died in septic shock after 28 days [21].…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings bewegen sich die berichteten Rezidivraten nach einer lokalen Exzision bei pT2-Karzinomen zwischen 0% und 67% [5,8,9,[12][13][14][16][17][18][19][20]. Für diese Diskrepanz gibt es eine Reihe von Gründen einschließlich uneinheitlicher Studienprotokolle mit unterschiedlichen therapeutischen Konzepten und divergierenden Kriterien für die Patientenselektion.…”
Section: Zusammenfassungunclassified
“…In dieser Studie betrug die lokale Rezidivrate nach transanaler Exzision eines pT2-Karzinoms 35%, was innerhalb der von anderen Untersuchern berichteten Spanne liegt (0-67%) [2,4,5,8,9,[12][13][14][16][17][18][19][20][21][22][23]. Außer der Patientenselektion gehören uneinheitliche postoperative Strategien und therapeutische Konzepte zu den Gründen für die von diesen Autoren berichteten stark divergierenden Raten.…”
Section: Diskussionunclassified
See 1 more Smart Citation